Conflict in the organization; An Analytical study - Benaoun , Zoubir; Deer , Mohamed (Social Empowerment Journal, 2021)
Conflict is a social phenomenon, It occurs in society, Between individuals and groups and within social organizations, It is also spread in organizations with a bureaucratic formation, Due to several factors and reasons. This phenomenon has been studied in many scientific fields, They drew several conclusions, However, in our study we are trying to search for the phenomenon of conflict in organizations from its conceptual and realistic point of view (As a process that has its causes and effects), To this end, we have dealt with a sociological analysis of the issue, By adopting the scientific, descriptive and analytical method, Finally, we concluded that the conflict Conceptually, It is related to many similar and synonymous concepts such as, The problem, Competition, disagreement ..., As for realistically within the organizations as a phenomenon and practice, it is very complex due to the multiplicity of its variables, the difference and intertwining of its causes and factors, and the variation in the fields in which it is generated, It may also be a positive phenomenon within the organization It may also have negative and destructive effects for the organization, and for individuals and groups, In this case, we find that each of the parties to the conflict process is trying to eliminate and remove its opponent With the intention of expanding his field of maneuver and achieving his personal goals at the expense of the other party and at the expense of the organization in which he lives.